Examining the Dimensions of Organizational Climate on Employee’s creativity in Jordanian Hotels - Al-Zoubi, Mohammad Issa; Alfandi, Ashraf Mohammad (The journal of contemporary issues in business and government, 2021)
The objective of this study is to develop and test a conceptual framework which linked the creativity of employees with four organizational climatic factors: the structure, obligation, rewards, and support, as well as the connection between creativity of employees and performance of employees. 432 employees in 18 luxury hotels in Jordan obtained data. The quantitative study is focused on an empirical exploratory factor, a basic linear regression analysis and the validity of the CFA factor solution. Results and recommendations in the study showed that the relationship between employee creativity and employee success affects the creativity of workers through different organizational factors. This study aims to strengthen the organizational environment and results for hotels in the area of hospitality in order to enhance their organizational climate.